Green finance for sustainable global growth - Tsai, Sang-Bing, 1973-; Shen, Chung-Hua; Song, Hua, 1969-; Niu, Baozhuang (Business Science Reference, 2019)
"This book provides relevant theoretical frameworks and the latest empirical research findings in the areas of green finance, internet finance and sustainable finance"--